Flushing of the deep Pacific Ocean and the deglacial rise of atmospheric CO 2 concentrations - Du, Jianghui; Haley, Brian A.; Mix, Alan C.; Walczak, Maureen H.; Praetorius, Summer K. (Nature Geoscience, 2018)
Enhanced overturning in the Pacific Ocean flushed carbon from the abyssal ocean to the atmosphere during the last deglaciation, according to authigenic neodymium isotope data.